Haven [compact disc, unabridged] - Hooper, Kay (Hooper, Kay. Bishop/Special Crimes Unit novel., 2012)
After a head injury brings on nightmares involving girls being tortured and murdered, Emma Rayburn contacts her estranged sister, Jessie, a psychic investigator.